PENGARUH PERENDAMAN AIR PDAM TERHADAP KEKERASAN ENAMEL GIGI PASKA HOME BLEACHING KARBAMID PEROKSIDA 20% - Aqshall Ilham Safatullah; Agung Satria Wardhana; Sherli Diana; Beta Widya Oktiani; Renie Kumala Dewi (Universitas Lambung Mangkurat, 2024)
Background: One of the treatments to overcome the problem of discolored teeth is to do tooth whitening or bleaching. The tooth whitening agent that is often used is carbamide peroxide which is applied directly to the tooth enamel surface. Several factors that can affect tooth enamel are the degree of acidity or potential hydrogen (pH), acid concentration, dissolving time and the presence of calcium-like ions. Communities in Banjarmasin City still frequently use PDAM water for consumption and for their daily needs. Objective: To analyze the effect of immersing PDAM water and distilled water on the hardness of tooth enamel after the application of 20% carbamide peroxide. Methods: This study used a true experimental method with a posttest-only with control group design consisting of 4 treatment groups namely positive control PDAM water, negative control Aquatic water, group 1 carbamide peroxide 20% and PDAM water, and group 2 carbamide peroxide 20% and distilled water. Tooth enamel hardness was measured using a Vickers microhardness tester. Results: analysis of the One Way Anova test with Post-Hoc Bonferroni showed that there was a significant difference in violence in each group (p>0.05). Conclusion: There is an effect of PDAM water after application of 20% carbamide peroxide on the hardness of enamel on teeth.Keywords: Carbamide Peroxide 20%, Discolored, Enamel Hardness, PDAM